Difference in oral absorption of ginsenoside Rg1 between in vitro and in vivo models - Han Min; Fang Xiao-ling (Acta Pharmacologica Sinica, 2016)
Aim: To clarify the cause of poor oral absorption of ginsenoside Rg1 (Rg1), the active ingredient in Panax notoginseng saponins (PNS) used for treating hemorrhage. Methods: Caco-2 cell monolayers were used as an in vitro model to study the transport mechanism of Rg 1 across the intestinal mucosa. Moreover, the serum concentration-time profiles after peroral (po ), intraduodenal (id), portal venous (pv) and tail venous (iv) administration of Rg1 in rats were compared to evaluate the first-pass effects in the stomach, intestine, and liver. Results: Up take of Rg 1 by Caco-2 cell monolayers was temperature-dependent, but was not influenced by cyclosporin A. The change in the apical pH produced no obvious effect on the uptake of Rg 1. The uptake and transport of Rg1 was non-saturable; whereas the flux from the apical compartment to the basolateral compartment (A-B) increased in a linear manner with the increase in concentration, indicating passive transport. An apparent permeability coefficient of (2.5 9 0.17)×10-7 cm/s (C0=1 mg/mL) predicted incomplete absorption. A significant difference was observed between the po (Fpo was 3.29% at a dose of 1500 mg/kg), id Fid was 6.60% at a dose of 1200 mg/kg) and pv (FPV was 50.56%) administration methods, and the barrier function of the intestine was more significant than those of the stomach and liver in the absorption process. Conclusion: Elimination in the stomach, large intestine and liver contributed to the low oral bioavailability of Rg1, but low membrane permeability might be a more important factor in determining the extent of absorption.